(untitled) (European Journal of Pure and Applied Mathematics, 2011)
In this study we suggest a new group decision-making method which is based on some basic fuzzy set operations. By using this method, we can get two types of results. First, we can identify which alternative is the best. The second result, a crucial point of this work, is the screening of decision-makers. The decision-makers should be serious and responsible in giving their opinions otherwise the process will eliminate them because of their inappropriate evaluations to the alternatives compared with that of the other decision-makers. We also discuss an application to demonstrate the process of the method.